2022
DOI: 10.1111/jvim.16452
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of isavuconazole in healthy cats after oral and intravenous administration

Abstract: Background: Isavuconazole is a triazole antifungal drug that has shown good efficacy in human patients. Absorption and pharmacokinetics have not been evaluated in cats.Objectives: To determine the pharmacokinetics of isavuconazole in cats given a single IV or PO dose.Animals: Eight healthy, adult research cats.Methods: Four cats received 100 mg capsules of isavuconazole PO. Four cats received 5 mg/kg isavuconazole solution IV. Serum was collected at predetermined intervals for analysis using ultra-high perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…4 Evaluation of isavuconazole pharmacokinetics in healthy cats demonstrated that both oral and intravenous of administration result in high serum concentrations and are generally well-tolerated. 11 In the case reported here, the addition of this antifungal agent resulted in clinical resolution of all lesions and clinical signs after three months of therapy, without adverse effects and no evidence of recurrence for a one-year follow-up period. To the best of the authors' knowledge, this is the first documented report of the clinical use of isavuconazole in veterinary medicine.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…4 Evaluation of isavuconazole pharmacokinetics in healthy cats demonstrated that both oral and intravenous of administration result in high serum concentrations and are generally well-tolerated. 11 In the case reported here, the addition of this antifungal agent resulted in clinical resolution of all lesions and clinical signs after three months of therapy, without adverse effects and no evidence of recurrence for a one-year follow-up period. To the best of the authors' knowledge, this is the first documented report of the clinical use of isavuconazole in veterinary medicine.…”
Section: Discussionmentioning
confidence: 49%
“…The most commonly reported adverse effects in people are nausea, vomiting and diarrhoea and to a lesser extent drug‐related hepatotoxicity 4 . Evaluation of isavuconazole pharmacokinetics in healthy cats demonstrated that both oral and intravenous routes of administration result in high serum concentrations and are generally well‐tolerated 11 . In the case reported here, the addition of this antifungal agent resulted in clinical resolution of all lesions and clinical signs after three months of therapy, without adverse effects and no evidence of recurrence for a one‐year follow‐up period.…”
Section: Discussionmentioning
confidence: 99%
“…< Adverse effects Vomiting was observed 6 and 8 h after dosing in two of four cats administered a single 100 mg ISA capsule. 23 In humans, AEs are infrequent and usually limited to mild nausea, vomiting and diarrhoea; also, hepatotoxicity and drug-drug inter actions are uncommon compared with other tri azole antifungals. 47 < Clinical use only single-dose IV and oral pharmacokinetic data (Tables 1 and 2) are available for cats.…”
Section: Isavuconazolementioning
confidence: 99%
“…47 < Clinical use only single-dose IV and oral pharmacokinetic data (Tables 1 and 2) are available for cats. 23 Reports of use of ISA in the field are not yet available. Based on in vitro data and human studies, ISA would not be indicated for empirical therapy of SoA in cats.…”
Section: Isavuconazolementioning
confidence: 99%